Memory B-Cell Development After Asymptomatic or Mild Symptomatic SARS-CoV-2 Infection. (27th July 2022) - Kato, Yu; Bloom, Nathaniel I; Sun, Peifang; Balinsky, Corey A; Qiu, Qi; Cheng, Ying; Jani, Vihasi; Schilling, Megan A; Goforth, Carl W; Weir, Dawn L; Ramos, Irene; Sealfon, Stuart C; et al.
Abstract: Background: The development of memory B cells after asymptomatic severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is not well understood. Methods: We compared spike antibody titers, pseudovirus neutralizing antibody titers, and memory B-cell responses among SARS-CoV-2 PCR-positive Marine recruits who either reported asymptomatic or symptomatic infection. Results: Thirty-six asymptomatic participants exhibited similar spike IgG titers, spike IgA titers, and pseudovirus neutralization titers compared to 30 symptomatic participants. Pseudovirus neutralization and spike IgG titers showed significant positive correlations with frequency of memory B cells. Conclusions: Among young adults, asymptomatic SARS-CoV-2 infection induced antibody and memory B-cell responses comparable to mild symptomatic infection. Abstract : Among young adults, the development of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2)–induced antibody and memory B-cell responses were similar after asymptomatic or mild symptomatic infection.